THE CORRELATION BETWEEN LEARNING STYLES AND ENGLISH LEARNING ACHIEVEMENT - Diah Ayu Novita Sari; R. Roswati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
English teacher has done many efforts to enhance students’ learning achievement, but in fact most of students still had difficulties in learning English. It is proofed from their scores in English subject. In relation to the problem above, the researchers is intended to find out whether there is correlation between students’ learning style and English learning achievement at seventh grade students of State Junior High School 5 Tapung. The instruments used in this research were questionnaire for students’ learning style and documentation for English learning achievement. The total population was 51 students. By using Chi Square formula through SPSS 22.00 in analyzing the data, the researchers found that the value of Sig. (2-sided) was 0.013, and the data was significant at the level of 5%. In other words, Sig. (2-sided) value is lower than 0.05 (Ho is rejected and Ha is accepted). It means that there is correlation between learning style and English learning achievement at seventh grade students of State Junior High School 5 Tapung. Based on the Cramer’s V value (0.353), the effect of students’ learning styles on their English learning achievement is categorized into large effect. It means that there is a high association between learning style and English learning achievement.